A wide band gap perovskite solar cell based on phosphonic acid derivative passivation

CN123021882APending Publication Date: 2026-10-30UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510556389.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

尽管这些材料在界面工程中能够有效调控能级排列、降低界面缺陷密度,并优化电荷传输路径,但其在覆盖性和取向性方面普遍表现较差

Benefits of technology

[0016]1.本发明在钙钛矿前驱体溶液中引入苯膦酸衍生物作为添加剂,制备了高结晶质量的钙钛矿薄膜,有效减少了钙钛矿体内与界面处的非辐射复合缺陷,延长了载流子寿命,从而提高了钙钛矿太阳能电池的效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123021882A_ABST
    Figure CN123021882A_ABST
Patent Text Reader

Abstract

The application belongs to the field of perovskite solar cells, and discloses a wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation, which has a laminated structure, and sequentially comprises a substrate, a transparent electrode, a hole transport layer, a perovskite active layer, an electron transport layer and a top electrode from bottom to top. The phenylphosphonic acid derivative is added to the perovskite active layer, and is also added to the SAMs hole transport layer, or an intermediate layer with the phenylphosphonic acid derivative is arranged between the hole transport layer and the perovskite active layer. By introducing the phenylphosphonic acid derivative as an additive, the perovskite thin film with high crystalline quality is prepared, the non-radiative recombination defects in the perovskite body and at the interface are effectively reduced, the carrier lifetime is prolonged, and thus the efficiency and stability of the perovskite solar cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of perovskite solar cells, specifically relating to a wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation and its preparation method. Background Technology

[0002] Perovskite solar cells utilize perovskite-type organometal halide semiconductors as light-absorbing materials. Due to the excellent photoelectric properties of perovskite semiconductors, including excellent carrier diffusion length, strong light absorption, low defect density, and solution processability, they are considered promising next-generation photovoltaic materials, belonging to the third generation of solar cells. In recent years, perovskite solar cells have attracted much attention due to their rapidly improving photoelectric conversion efficiency. These materials not only have low raw material costs but also very simple manufacturing processes. Narrow bandgap lead-based perovskite solar cells (LPSCs) refer to cells that use perovskite materials with a bandgap of less than 1.7 eV as active materials. In the past decade, their photoelectric conversion efficiency (PCE) has rapidly increased from 3.8% to over 26%, approaching their theoretical efficiency limit (Shockley-Queisser limit) of 33%. As a crucial technology for next-generation high-efficiency solar cells, wide-bandgap perovskite solar cells using perovskite materials with bandgap ranges from 1.7 eV to 2.3 eV have been widely applied in perovskite-silicon tandem devices and all-perovskite tandem devices. By optimizing the spectral absorption characteristics of wide-bandgap perovskite materials, the photoelectric conversion efficiency of these cells can be significantly improved, providing a potential technological path to breaking the SQ theoretical limit. However, despite the significant theoretical advantages of wide-bandgap perovskite solar cells, they still face a series of technical bottlenecks in practical applications, particularly in terms of device performance repeatability and efficiency stability.

[0003] Currently, self-assembled monolayers (SAMs), commonly used as hole transport layers in wide-bandgap perovskite solar cells, exhibit significant limitations in practical applications. Although these materials can effectively control energy level alignment, reduce interface defect density, and optimize charge transport paths through interface engineering, they generally perform poorly in terms of coverage and orientation. These issues directly affect the film quality and interface stability of perovskite films, thus limiting further improvements in the photoelectric conversion efficiency and long-term operational stability of perovskite photovoltaic devices. Furthermore, the inevitable precipitation of lead iodide (PbI2) impurities during the annealing process of perovskite films and subsequent storage also severely impacts device performance. These precipitated PbI2 often accumulate at the upper interface of the perovskite film, significantly reducing the crystallinity of the perovskite and hindering carrier transport at the interface. The increase in interface defects and the exacerbation of carrier recombination further weaken the device's efficiency. Simultaneously, the accumulation of PbI2 impurities may also induce other harmful chemical reactions, further accelerating device performance degradation.

[0004] In 2024, Li Changzhi's group (Huang Y, Yan K, Wang X, et al. High-Efficiency Inverted Perovskite Solar Cells via In Situ Passivation Directed Crystallization[J]. Advanced Materials, 2024, 36(41): 2408101.) incorporated MeO-2PACz and other SAMs materials into narrow-bandgap lead-based perovskite solutions, promoting the formation of vertically oriented grains and improving the uniformity of crystal size. However, when this method was applied to wide-bandgap perovskite materials, no significant efficiency improvement was observed. Furthermore, since the SAMs material structure contains only one phosphonic acid group, it does not react with Pb in the perovskite. 2+Plasma binding is weak, and passivation is not obvious. In 2024, Li Xuanhua's group (He X, Chen H, Yang J, et al. Enhancing hole transport uniformity for efficient inverted perovskite solar cells through optimizing buried interface contacts and suppressing interface recombination[J]. Angewandte Chemie, 2024, 136(52):e202412601.) introduced p-XPA containing bisphosphonic acid groups into NiO X / Me-4PACz acts as an interface layer between the perovskite and the substrate, smoothing the interface and optimizing the interfacial contact. Simultaneously, the bisphosphonic acid groups of p-XPA and the Pb in the perovskite... 2+ It can undergo chelation and react with FA. + Hydrogen bonds are formed, which effectively suppresses nonradiative recombination loss at the bottom interface. However, this method only has a passivating effect at the interface between the SAMs layer and the perovskite, and its effect on the internal crystallization of the perovskite and the regulation of the upper interface is not obvious.

[0005] Therefore, methods to improve device performance by modulating various aspects, including the interface between SAMs and the perovskite in wide-bandgap perovskite solar cells and within the perovskite body, are urgently needed. Summary of the Invention

[0006] In view of the shortcomings of the existing technology, the present invention provides a wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation. It aims to improve the passivation effect by regulating the SAMs at the interface between the perovskite and the perovskite, as well as in the perovskite body, thereby improving the efficiency and stability of perovskite photovoltaic devices and accelerating the practical application of perovskite solar cells.

[0007] To achieve its objectives, the present invention employs the following technical solution:

[0008] A wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation has a stacked structure, consisting of a substrate (transparent substrate or silicon substrate) - transparent electrode - hole transport layer - perovskite active layer - electron transport layer - top electrode from bottom to top. The characteristic of the solar cell is that phenylphosphonic acid derivative is added to the perovskite active layer.

[0009] Furthermore, the hole transport layer is prepared using a solution of self-assembled monolayer (SAM) materials. A phenylphosphonic acid derivative is also added to the hole transport layer, or an intermediate layer of phenylphosphonic acid derivative is disposed between the hole transport layer and the perovskite active layer. By adding a phenylphosphonic acid derivative to the SAMs, or by placing the phenylphosphonic acid derivative between the SAMs layer and the perovskite active layer, the wettability of the perovskite material can be improved, allowing for more uniform film formation of the perovskite material and enhancing the stability of the battery.

[0010] Further, the phenylphosphonic acid derivative is at least one of 1,4-phenyldiphosphonic acid, biphenyl-4,4-diphosphonic acid, and 1,3,5-phenyl-tri-p-phenylphosphonic acid.

[0011] Furthermore, in the perovskite precursor solution used to prepare the perovskite active layer, the concentration of the added phenylphosphonic acid derivative is 0.5–2 mg / mL.

[0012] Furthermore, in the solution used to prepare the self-assembled monolayer material for the hole transport layer, the concentration of the added phenylphosphonic acid derivative is 0.3–1 mg / mL.

[0013] Furthermore, the perovskite material used to prepare the perovskite active layer is (Cs,FA,MA)Pb(I,Br)3.

[0014] Furthermore, a passivation layer is provided between the perovskite active layer and the electron transport layer, specifically ethylenediamine bromide (EDABr2).

[0015] Compared with existing technologies, this invention can achieve high-efficiency and high-stability perovskite solar cells for the following reasons:

[0016] 1. This invention introduces phenylphosphonic acid derivatives as additives into the perovskite precursor solution to prepare perovskite thin films with high crystallinity, effectively reducing non-radiative recombination defects in the perovskite body and at the interface, extending carrier lifetime, and thus improving the efficiency of perovskite solar cells.

[0017] 2. This invention introduces a phenylphosphonic acid derivative as an additive into the perovskite precursor solution. Because the additive reacts with Pb in the perovskite... 2+ The chelation effect, and the interaction between phosphonic acid groups and FA + The hydrogen bonds formed by organic cations reduce interfacial defects between the perovskite and the carrier transport layer, increasing the carrier transport rate and thus improving the efficiency of perovskite solar cells. Simultaneously, the additives and Pb in the perovskite... 2+ The chelation effect effectively inhibited the precipitation of PbI2 on the perovskite surface, thereby suppressing further decomposition of the perovskite and improving the stability of the device.

[0018] 3. By further adding phenylphosphonic acid derivatives to SAMs, or placing phenylphosphonic acid derivatives between the SAMs layer and the perovskite active layer, the present invention can improve the orientation and uniformity of SAMs, thereby improving the wettability of the perovskite precursor solution in the SAMs layer, and thus preparing a perovskite film with better crystallinity.

[0019] 4. The additive strategy of the present invention can also be applied to perovskite silicon tandem solar cells to improve device efficiency, and has broad application prospects. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the device structure of the perovskite solar cell of the present invention.

[0021] Figure 2 These are photoluminescence intensity diagrams of several groups of perovskite thin films prepared in Example 1 of the present invention.

[0022] Figures 3 to 6 The JV curves of the perovskite solar cells constructed in the control group, experimental group 1, experimental group 2, and experimental group 3 in Example 1 of this invention are shown in sequence.

[0023] Figure 7 This is a comparison chart of the device placement stability between the control group and experimental group 3 in Example 1.

[0024] Figure 8 This is a SEM image of the perovskite active layer surface of the control group in Example 1.

[0025] Figure 9 This is a SEM image of the surface of the perovskite active layer in experimental group 3 of Example 1.

[0026] Figure 10 This shows the coating of perovskite active layers prepared on different hole transport layer surfaces in Example 2. Detailed Implementation

[0027] To provide a better understanding of the technical features, objectives, and beneficial effects of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the present invention is not limited to these embodiments.

[0028] Example 1

[0029] This embodiment prepares a wide-bandgap perovskite solar cell according to the following steps:

[0030] 1. The FTO transparent glass substrate was ultrasonically cleaned for 15 minutes each with deionized water, glass cleaner, deionized water, acetone, isopropanol, and ethanol. After drying in an oven, it was cleaned with a UV ozone generator for 15 minutes. Then the substrate was transferred to a glove box with a nitrogen atmosphere.

[0031] 2. Mix Me-4PACz and MeO-2PACz at a mass ratio of 3:1, then dissolve 0.4 mg of the mixture in 1 mL of ethanol to prepare a SAMs solution. Then spin-coat the prepared SAMs solution onto an FTO transparent glass substrate at a speed of 4000 r / s for 30 s, and then anneal at 100 °C for 10 minutes to form a hole transport layer.

[0032] 3. Prepare perovskite precursor solution. Spin-coat the prepared perovskite precursor solution at a speed of 5000 r / s for 40 s. During the spin-coating process, add 0.2 mL of anisole solution dropwise. Then anneal at 100 °C for 15 minutes to form a perovskite active layer.

[0033] The components of the perovskite precursor solution are as follows:

[0034] Control group: 19.5 mg CsI, 25.1 mg MAI, 206.4 mg FAI, 165.2 mg PbBr2 and 484.0 mg PbI2 were dissolved in 1 mL of a mixed solvent of DMF and DMSO (the volume ratio of DMF to DMSO was 4:1).

[0035] Experimental group 1: 0.001 g of 1,4-phenylenediamine was added to 1 mL of perovskite precursor solution (control group).

[0036] Experimental group 2: 0.001 g of biphenyl-4,4-diphosphonic acid was added to 1 mL of perovskite precursor solution (control group).

[0037] Experimental group 3: 0.001 g of 1,3,5-benzene-trip-phenylphosphonic acid was added to 1 mL of perovskite precursor solution (control group).

[0038] 4. Dissolve 1 mg of EDABr2 in 1 mL of IPA solvent to obtain an EDABr2 solution. Spin-coat the prepared EDABr2 solution onto the perovskite active layer at a speed of 4000 r / s for 30 s, and anneal at 100 °C for 10 minutes to form a passivation layer.

[0039] 5. Sequentially deposit 20nm thick C on the passivation layer. 60 Thin film and 7nm thick BCP film are used as electron transport layers.

[0040] 6. Evaporate a 90nm thick gold electrode.

[0041] Figure 2 The figures show the photoluminescence intensity of several perovskite thin films prepared in this embodiment. It can be seen from the figures that the addition of phenylphosphonic acid derivatives can significantly improve the crystallinity of the film, and the addition of 1,3,5-benzene-tris-p-phenylphosphonic acid and 1,4-benzenediphosphonic acid has a better effect.

[0042] Figures 3-6 The JV curves of several groups of perovskite solar cells constructed in this embodiment are shown in Table 1, which are the control group, experimental group 1, experimental group 2 and experimental group 3 in sequence. Their performance parameters are shown in Table 1. It can be seen that the addition of phenylphosphonic acid derivative can significantly improve the photoelectric conversion efficiency of the device.

[0043] Table 1

[0044]

[0045]

[0046] Figure 7 The figures show the device stability in the control group and experimental group 3 (placed in a glove box under nitrogen atmosphere at room temperature). The figures demonstrate that the addition of phenylphosphonic acid derivatives significantly improves device stability.

[0047] Figure 8 , 9 The images show SEM images of the perovskite active layer surfaces of the control group and experimental group 3, respectively. The white bright spots distributed at the grain boundaries are lead iodide precipitation. It can be seen from the images that the experimental group inhibited the precipitation of lead iodide.

[0048] Example 2

[0049] In this embodiment, the hole transport layer and perovskite active layer of a wide-bandgap perovskite solar cell are fabricated on an FTO transparent glass substrate (a portion of the substrate surface is designated as an FTO-free region) using the same method as in Example 1 (the perovskite precursor solution used is the same as the control group in Example 1). The only difference is that the SAMs solutions in step 2 are:

[0050] Control group A: 0.4 mg Me-4PACz was dissolved in 1 mL of ethanol to prepare SAMs solution;

[0051] Control group B: A SAMs solution was prepared by dissolving a mixture of 0.4 mg Me-4PACz and 0.25 mg MeO-2PACz in 1 mL of ethanol;

[0052] Experimental group C: A SAMs solution was prepared by dissolving a mixture of 0.4 mg Me-4PACz and 0.25 mg 1,4-benzenediphosphonic acid in 1 mL of ethanol;

[0053] Experimental group D: SAMs solution was prepared by dissolving a mixture of 0.4 mg Me-4PACz and 0.25 mg 1,3,5-benzene-trip-phenylphosphonic acid in 1 mL of ethanol.

[0054] The surface morphology of the perovskite active layers formed on different hole transport layers was observed, and the results are as follows: Figure 10As shown in the figure, the samples from left to right correspond to control group A, control group B, experimental group C, and experimental group D, respectively. The results show that all four groups of samples can form a continuous and complete capping layer on the FTO conductive substrate surface. However, in the area without FTO, the coverage of different groups differs: control group A failed to achieve complete coverage, control group B achieved large-area coverage but still had local defects, while experimental groups C and D both achieved complete coverage. These comparative results indicate that the introduction of additives significantly improves the wettability of the perovskite precursor solution on the glass substrate, thereby effectively improving the uniformity and capping quality of the film.

[0055] In summary, during the preparation of perovskite thin films, this invention introduces phenylphosphonic acid derivatives into the SAMs solution, resulting in a well-oriented SAMs layer and improving the coating properties of perovskite on the SAMs layer surface. Simultaneously, the introduction of phenylphosphonic acid derivatives into the perovskite solution slows down the crystallization rate of perovskite during annealing, improves the crystal quality of perovskite, and inhibits the precipitation of lead iodide, yielding a high-quality perovskite thin film with large and dense grain size. Based on this, the conversion efficiency of the wide-bandgap perovskite solar cell reached 22.8%, and the device efficiency remained above 95% after 40 days of storage.

Claims

1. A wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation, comprising a stacked structure, wherein from bottom to top are a substrate, a transparent electrode, a hole transport layer, a perovskite active layer, an electron transport layer, and a top electrode, characterized in that: A phenylphosphonic acid derivative is added to the perovskite active layer.

2. The wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation according to claim 1, characterized in that: The hole transport layer is prepared by means of a solution of a self-assembled monomolecular membrane material; a phenylphosphonic acid derivative is also added to the hole transport layer, or an intermediate layer of phenylphosphonic acid derivative is provided between the hole transport layer and the perovskite active layer.

3. The wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation according to claim 1 or 2, characterized in that: The phenylphosphonic acid derivative is at least one of 1,4-phenyldiphosphonic acid, biphenyl-4,4-diphosphonic acid, and 1,3,5-phenyl-tri-p-phenylphosphonic acid.

4. The wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation according to claim 1, characterized in that: In the perovskite precursor solution used to prepare the perovskite active layer, the concentration of the added phenylphosphonic acid derivative is 0.5–2 mg / mL.

5. The wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation according to claim 2, characterized in that: In the solution used to prepare the self-assembled monolayer material for the hole transport layer, the concentration of the added phenylphosphonic acid derivative is 0.3–1 mg / mL.

6. The wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation according to claim 1, characterized in that: The perovskite material of the perovskite active layer is (Cs,FA,MA)Pb(I,Br)3.

7. The wide-bandgap perovskite solar cell based on phenylphosphonic acid derivative passivation according to claim 1, characterized in that: A passivation layer is also provided between the perovskite active layer and the electron transport layer.